The Effect of Budget Performance and Financial Management Transparency on the Financial Performance of Local Governments with Public Accountability as a Moderation Variable - Munandar, Ahmad; Munir, Abd. Razak (Pattimura Proceeding, 2026)
This study examines how budget performance and transparency of financial management impact the financial performance of local governments, with public accountability serving as a moderating factor. The study focuses on the Central Mamuju Regency Government, involving 65 participants, including the head of Regional Working Unit. field heads, sub-field heads, and officials responsible for regional financial management. A quantitative research method was employed, and questionnaires were used for data collection. The data were analyzed using Moderated Regression Analysis. The findings indicate that both budget performance and financial management transparency positively and significantly influence the financial performance of local governments. Furthermore, public accountability enhances the impact of budget performance and financial management transparency on regional financial performance. These results underscore the critical role of bolstering public accountability in enhancing the financial performance of local governments.